(untitled) (American Journal of Pedagogical and Educational Research, 2026)
This research sought to examine the effect of traditional therapy on athletes’ recovery from injury in Bamenda North West Region of Cameroon. Football athletes are susceptible to injuries due largely to the physical contact; overtraining and psychological demands for outstanding performance on the field of play. This study was conducted in Bamenda elite 1 and 2 teams; PWD, YOSA, Bafut Rangers Foncha Street and Bafmeng United. The research design used in this study was concurrent mixed method design. The population was divided in to both the target and accessible population of the study. The researcher used the purposive sampling technique to select players of each team with sampling size of 23 injured players to work with. Descriptively, the data was presented on tables, frequencies, means and percentages. Regression was used analyze quantitative data, content thematic analysis was used to analyze qualitative data results shows that traditional therapy has a significant effect on athlete’s recovery from injury at 0.01 level of significance and 14.5% of the variations in athletes’ recovery from injury can be accounted for by their use of traditional therapy such as herbal medicine leaves, herbal oil, and consulting traditional doctors for massage when injured. Result shows that traditional therapy has a significant effect on athlete’s recovery from injury at 0.01 level of significance and 8.6% of the variations in athletes’ recovery process from injuries can be explained by the use of massage therapy such as cold and hot water massages. The study made recommendations to the Ministry of Sports and Physical Education, the government should offer support and funding towards traditional therapy centers that specialize in treating sports- related injuries. Ensure that players receive prompt and appropriate treatment for their injuries to prevent further complications. All in all, it was found out that, traditional therapy helps athletes to recover from injury. For recommendations, to ministry of sports and physical education, the government should offer support and funding towards traditional therapy centers that specialize in treating sports- related injuries. For further studies, my research was a mixed method research, so, another researcher can conduct a purely quantitative study or purely qualitative study.